Improving Understanding Of HIV/AIDS Disease And Effort For Their Prevention/Management For SMA Trensains Muhammadiyah Sragen - Rejeki, Mirah; Risqulloh, Ludfiyah (Prosiding University Research Colloquium, 2022)
HIV (human immunodeficiency virus) is a virus that destroys the immune system by infecting and destroying CD4 cells. The more CD4 cells that are destroyed, the weaker your immune system will be, making you more susceptible to various diseases. HIV infection that is not treated immediately, will develop into a serious condition called AIDS (Acquired Immune Deficiency Syndrome). AIDS is the final stage of HIV infection. At this stage, the body's ability to fight infection is completely lost. Currently there is no drug to treat HIV and AIDS. But there are drugs to slow the progression of the disease, and can increase sufferers' life expectancy. Based on data from the Indonesian Ministry of Health, during 2016 there were more than 40 thousand cases of HIV infection in Indonesia. HIV is most commonly found in heterosexuals, followed by male sex men (MSM) and injecting users. In the same year more than 7000 people suffered from AIDS with the death toll of more than 800 people. The latest data from the Ministry of Health of the Republic of Indonesia shows that from January to March 2017, more than 10,000 reports of HIV infection have been recorded, and no less than 650 AIDS cases in Indonesia. From the Health profile in Kab. Sragen was found in 2014, 21 people with HIV, as many as 55 AIDS sufferers. In 2014 it was found the death of 9 patients with AIDS. The purpose of this community service is to increase understanding of the younger generation, especially students of SMA Trensains Muhammadiyah Sragen who are the nation's next generation in Banaran Village, Connectmacan District, Sragen Regency, regarding HIV/AIDS, its causes, transmission, prevention and risks. Results: The target number is 61 people with an age limit of 15-25 years, the method of socialization is by giving power points and given a pre-test before socialization, and post-test after socialization there is an increase in understanding in SMA Trensains Muhammadiyah Sragen students from the results of pre-test and post-test. - community service test. Conclusion: It is very important for the students of SMA Trensains Muhammadiyah Sragen to increase their understanding of HIV/AIDS, so that our young generation does not have a bleak future and gives birth to strong successors so that they are more careful in their daily interactions and reduce the prevalence of HIV/AIDS sufferers.